Pengaruh Ekstrak Orthosiphon Aristatus terhadap Pertumbuhan Mikroorganisme Uji dalam Praktikum Mikrobiologi Dasar - Rezky Maulidiya; Ardi Mustakim (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Orthosiphon aristatus is a medicinal plant that has the potential as a natural antibacterial agent. This study aims to evaluate the effect of cat's whiskers leaf extract on microbial growth using Nutrient Agar (NA) media with variations in extract concentrations of 100 gr, 50 gr, and 25 gr. Antibacterial activity tests were carried out using the well diffusion paper disk method, and observations of microbial growth inhibition zones were carried out after incubation for 24 hours at 37°C. The test results showed that there was inhibition of microbial growth that varied according to the concentration of the extract used; a concentration of 100 gr gave the largest inhibition zone compared to 50 gr and 25 gr. Data analysis showed that increasing extract concentration was directly proportional to increasing antibacterial effectiveness. These findings indicate that Orthosiphon aristatus leaf extract has the potential as a natural antibacterial that is effective in inhibiting microbial growth in NA media, so it has the potential to be developed as an active ingredient in pharmaceutical formulations.